PERAN ETIKA, PROFESIONALISME, DAN KUALITAS AUDITOR DALAM IMPLEMENTASI TANGGUNG JAWAB SOSIAL PERUSAHAAN - Windi Larasati; Widia Sri Kartika Sari; Larasati; Miftahurrahmah Sinaga; Fitri Yani Panggabean (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the influence of ethics, professionalism, and auditor quality on the implementation of corporate social responsibility (CSR). The research approach used is a literature study that includes an analysis of previous research relevant to the issue. The results showed that high ethics, consistent professionalism, and good auditor quality can play a significant role in encouraging transparent and responsible CSR implementation and can make a positive contribution to increasing stakeholder trust. This research is expected to contribute to the development of more responsible audit practices in every company and public agency.